Social orphanhood – towards learning and understanding to bring help - Kiszka, Monika (Kultura-Społeczeństwo-Edukacja, 2021)
The goal of the article is to describes the impact of parental behaviour on children’s lives. The main body discusses the neglect of parental duties and the misguided attitude towards raising children exhibited by some parents. Additionally, the article describes the phenomenon of orphanhood and its connection with the problems that some parents are unable to cope with. The second part focuses on the most harmful consequences of certain negative behaviours exhibited by some parents. The final part of the article is a list of personality disorders and the other problems that children suffering from social orphanhood may experience.